2016
DOI: 10.1111/1365-2745.12569
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nutrient dynamics in an African savanna: local biotic interactions outweigh a major regional rainfall gradient

Abstract: 1. Nutrient availability in terrestrial ecosystems has been found to vary along regional climatic and soil gradients and drive variation in plant community composition and vegetation structure. However, more local biotic feedbacks also affect nutrient availability, but their importance in determining vegetation structure relative to regional drivers is yet unclear. 2. Mesic African savannas form a transition zone between the dry grasslands with relatively low nitrogen availability (indicated by low plant N:P r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…8). These are factors that influence ecohydrological processes such as the propensity to form overland flows during rainfall events (Valentin et al, 1999). The results are in agreement with a global study on the biogeography of PVPs by Deblauwe et al (2008), who found similar effects in regions with strong seasonal variation in temperature and more constant rainfall (Australia and Mexico) and in regions with distinct rainfall seasonality but more constant temperatures (Africa).…”
Section: Woody Plant Aggregation and The Occurrence Of Periodic Vegetsupporting
confidence: 90%
See 3 more Smart Citations
“…8). These are factors that influence ecohydrological processes such as the propensity to form overland flows during rainfall events (Valentin et al, 1999). The results are in agreement with a global study on the biogeography of PVPs by Deblauwe et al (2008), who found similar effects in regions with strong seasonal variation in temperature and more constant rainfall (Australia and Mexico) and in regions with distinct rainfall seasonality but more constant temperatures (Africa).…”
Section: Woody Plant Aggregation and The Occurrence Of Periodic Vegetsupporting
confidence: 90%
“…Woody cover is fundamentally a function of crown sizes and crown density and by studying these components individually, it is possible to attain important insight into the function of ecosystems and what ecosystem services they provide. Two landscapes with similar woody cover but different sizes of individual trees will sequester different amounts of carbon (Shackleton and Scholes, 2011), harbor different fauna (Riginos and Grace, 2008), and differ in biogeochemical dynamics (Veldhuis et al, 2016a). The level of spatial aggregation among woody plants can help us understand facilitative and competitive processes determining survival of seedlings and saplings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although uncertainty regarding N losses by fire is large (Gruber and Galloway, 2008), the general agreement with observations strengthens our finding of the important role of fire in the terrestrial N budget. Specifically for savannah ecosystems, the influence of fire on N dynamics is further supported by field and remote sensing studies (Veldhuis et al, 2016;Chen et al, 2010).…”
Section: Firementioning
confidence: 91%